Mitigating the Effects of Intereference in a Multipath Prone Environment for a DVB-T Transmission - Oluwaseun Yinka Alabi; Michael Kolawole (Institute of Advanced Engineering and Science, 2015)
This paper develops a novel simulation method that seeks to mitigate the effects of interference in a multipath prone environment for a DVB-T transmission by using the AWGN and the Multipath Rayleigh Fading Channel. The channel parameters were optimized until desired result was obtained. The reception performance of the DVB-T system shows that interference though not totally eliminated, can be minimized while transmitting in a multipath prone environment.